Primary Pulmonary Sarcomatoid Carcinomas: a Report of two Cases - H. Ziyadi; G. Salhi; B. Daher; N. Yassine (International Journal of Scientific Research and Innovative Studies, 2026)
Sarcomatoid carcinomas (SC) are rare non-small cell lung cancers (NSCLCs), accounting for less than 1% of lung cancers. They are characterised by a spindle-shaped or giant cell component suggestive of a sarcoma. We report two cases in patients aged 80 and 75, both former smokers, illustrating the extreme aggressiveness of this condition. In both cases, the course of the disease was marked by rapid local and metastatic progression, leading to death within six months of diagnosis. This study highlights the diagnostic challenges and poor prognosis of these tumours, which are often resistant to conventional therapies. Keywords: Sarcomatoid carcinoma, NSCLC, Rare tumour, Prognosis, Tumour aggressiveness. Received Date: February 22, 2026 Accepted Date: March 14, 2026 Published Date: April 02, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/670